197 Role of a Dietitian in a Specialist Memory Assessment and Support Service - Improving Brain Health. (16th September 2019) - Fox, Emma; White, Sarah; Digan, Eimear; Feehan, Sinead; McHale, Cathy; Dookhy, Joshi; Kennelly, Sean
Abstract: Background: Dementia cases are rising nationally due to our ageing population and is associated with a multitude of nutritional consequences. Both obesity and malnutrition are strongly implicated in the progression of cognitive decline. From diagnosis onwards, nutritional intervention is important to improve patient outcomes. Methods: In order to highlight the important role of a dietitian, a retrospective analysis of 142 patients attending the tertiary memory assessment and support service from 2018 to 2019 was performed. Demographic, cognitive, anthropometric, and nutritional data was compiled from the case note review and biochemical laboratory results. This data was analysed using Microsoft Excel (2013) to study prevalence and relationships of variables in this cohort. Results: A significant proportion of this population were overweight (41.2%) and obese (18.6%). Nearly half the population were at risk of malnutrition (44.1%) or malnourished (3.9%). In this cohort, 18.6% were characterised as frail. Only one individual had a severe clinical dementia rating score (CDR), 19.2% had a moderate and 28.2% had a mild CDR. Half (50.5%) of participants had some level of abnormal eating habits. Higher prevalence of malnutrition, frailty and higher CDR was associated with increased age. Up to 60% of those with normal nutritional status had a CDR of 0 or 0.5. As MNA score worsened, the incidence of robust individuals decreased linearly. Prevalence of frailty increased as CDR score increased. Of those with a mild CDR, 70% were overweight or obese. Those with high Cambridge Behavioural-Inventory (CBI-R) eating habit scores generally had lower CDRs. Conclusion: Patients attending the memory service are experiencing a multitude of nutritional challenges such as disordered eating habits, overweight and obesity, malnutrition risk and frailty which are associated with cognitive decline and worse health outcomes. Nutritional support and dietetic input as part of the post-diagnostic care-pathway is required to promote brain health and mitigate unnecessary decline.